(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article examines the comparative characteristics of educational issues in Eastern and Western pedagogy. It analyzes the goals, objectives, methods, and techniques of education in both pedagogical systems, highlighting their similarities and differences. The significance of integrating approaches based on spirituality and traditional values in Eastern pedagogy with those emphasizing personal freedom and critical thinking in Western pedagogy is emphasized. As a result of the study, methodological recommendations have been developed to harmonize the positive aspects of Eastern and Western pedagogy.